The association between double-lumen tube versus bronchial blocker and postoperative pulmonary complications in patients after lung cancer surgery - Liu, Wei; Jin, Fan; Wang, He-Mei; Yong, Fang-Fang; Wu, Zhen; Jia, Hui-Qun (Frontiers in Oncology, 2022)
Background Both double-lumen tube (DLT) and bronchial blocker (BB) are used for lung isolation in patients undergoing lung cancer surgery. However, the effects of different devices for lung isolation remain inconclusive. Present study was designed to investigate the association between the choice of the two devices and postoperative pulmonary complications (PPCs) in patients with lung cancer. Methods In this retrospective cohort study, patients who underwent lung cancer surgery between January 1, 2020 and October 31, 2020 were screened. Patients were divided into two groups according to different devices for lung isolation: DLT group and BB group. Primary outcome was the incidence of a composite of PPCs during postoperative in-hospital stay. Results A total of 1721 were enrolled for analysis; of them, 868 received DLT and 853 BB. A composite of PPCs was less common in patients with BB (25.1%, [214/853]) than those received DLT (37.9% [329/868]; OR 0.582; 95% CI 0.461-0.735; P<0.001). Respiratory infection was less common in BB group (14.4%, [123/853]) than DLT group (30.3%, [263/868], P<0.001). The incidence of non-PPCs complications was not statistically significant between the 2 groups. Conclusions For patients undergoing surgery for lung cancer, the use of BB for lung isolation was associated with a reduced risk of PPCs when compared with DLT.